Effect of effective microorganisms on production parameters and water quality in semi-intensive white shrimp Litopenaeus vannamei farming. - Toro M., Dreime (2021)
The objective of this study was to assess the effect of effective microorganisms (EM) on the growth and survival of Litopenaeus vannamei “white shrimp” reared in a semi-intensive system in the region of Tumbes, Peru. Post-larvae (PLs) of approximately 0.02 g were cultured (15 PLs/m2) in four ponds (E) distributed in two groups: E1-E2 as controls (without EM), and E3-E4 with EM supplementation. EM was added to feed daily and directly to the water weekly. From each pond, 200 shrimps were captured weekly to assess the growth parameter (weight). Analysis of variance and Tukey’s test were used to determine significant differences in weight growth. The water physical- chemical parameters were monitored (daily and weekly), while, organic matter was determined at the beginning and at the end of the experiment. Finally, the economic indicators of the study were evaluated. Significant differences in weight growth were found between groups, in favor of the EM group since the fifth week of cultivation, but not in replicates. Higher gross productions were obtained: 1,001.28 kg/ha (E3) and 1,028.90 kg/ha (E4), and a better Food Conversion Factor (FCA): 1.11-0.31 (E3) and 1.23-0.29 (E4) in the EM group. Survivals of less than 50% were recorded in both groups. The physical-chemical parameters of the pond water remained within the optimal values for the studied species. Percentages of organic matter decreased at the end of the experiment in ponds of the EM group; economic indicators were also higher in this group, highlighting the return per dollar invested (EM: 2.76; control:1.20). In conclusion, the addition of EM improved parameters of production and FCA of L. vannamei, as well as water quality, generating better economic revenues.